Immunodiagnostic Capabilities of Anti-Free Immunoglobulin Light Chain Monoclonal Antibodies - Davern, Sandra (2008)
Overproduction of plasma cell-derived monoclonal free κ or λ immunoglobulin light chains (FLCs) is a characteristic hallmark of multiple myeloma, AL amyloidosis, and light chain deposition disease. Since these components serve as unique cellular and serologic biomarkers, their detection and quantitation has diagnostic, therapeutic, and prognostic import. In this regard, we have developed monoclonal antibodies (mAbs) that specifically recognize the κ or λ FLC products of all known human variable and constant region light-chain genes. We now report the results of our studies that have demonstrated the capability of these reagents to measure, in a modified fluid-phase capture ELISA, serum κ and λ FLCs at concentrations as low as 5 and 15 ng/mL, respectively. The mAb–based ELISA has greater sensitivity and reproducibility then does the commercially available immunoturbidimetric assay which utilizes polyclonal anti-FLC antibodies. Additionally, the mAbs can immunostain monoclonal FLC-producing plasma cells, as well as pathologic light chain-related amyloid and non-fibrillar tissue deposits. Our anti-FLC mAbs, with their high degree of reactivity and versatility, may provide an invaluable tool in the diagnosis and management of patients with light chain-associated disease.